Enhancing Learning Motivation of Students with Special Needs Using Learning Video - Kholis, Khoerul Umam; Kustiyono, Kustiyono (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
This study aims to evaluate the implementation of learning video entitled Cycling is Fun on learning practice of students grade XII-B of public special education in Semarang. The research uses quantitative descriptive analysis by involving six deaf special need students through observation, testing, interview and document search. The research result shown that the learning video could (1) create a conducive learning atmosphere of 88%, (2) motivate the students’ motivation of 96%, (3) build a students’ discipline reached 95%, (4) encourage students’ activeness reached 85%, and (5) affect the average of students’ learning outcomes with a score of 84,43. Student learning activities look very good and they are able to reach the learning outcome standard. Thus, it can be concluded that the use of the learning video with the title Cycling is Fun is very well used to learn English subject for student with deaf special need. Abstrak Tujuan penelitian ini adalah mengevaluasi penggunaan media video pembelajaran bertema cycling is fun pada aktivitas belajar siswa kelas XII-B SLB Negeri Semarang. Penelitian menggunakan metode deskriptif-kuantitatif dan melibatkan enam siswa tunarungu melalui observasi, tes, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa media video pembelajaran tema cycling is fun mampu (1) menciptakan suasana belajar kondusif sebesar 88%, (2) memotivasi belajar siswa sebesar 96%, (3) membangun kedisiplinan siswa mencapai 95%, (4) mendorong keaktifan belajar siswa mencapai 85%, dan (5) memengaruhi rata-rata nilai hasil belajar siswa dengan skor 84,43. Aktivitas belajar siswa terlihat sangat baik dan mereka mampu mencapai standar ketuntasan hasil belajar. Dengan demikian dapat disimpulkan bahwa penggunaan media video pembelajaran tema cycling is fun sangat baik digunakan untuk pembelajaran Bahasa Inggris oleh siswa tunarungu.